Anti-inflammatory function of ginsenoside Rg1 on alcoholic hepatitis through glucocorticoid receptor related nuclear factor-kappa B pathway - Gao, Yan; Chu, Shifeng; Li, Jingwei; Li, Jianping; Zhang, Zhao; Xia, Congyuan; Heng, Yang; Zhang, Meijin; Hu, Jinfeng; Wei, Guining; Li, Yueting; Chen, Naihong (Journal of ethnopharmacology, 2015)
Ginseng is the dried root of Panax ginseng C.A. Mayer. Since ancient times, ginseng has been used as one kind of treatment drug or tonic in China and even other eastern countries like Korea and Japan. Pharmacological active chemical ingredients and its extract of ginseng are a mixture of triterpenoid saponins, collectively called ginsenosides. Among them, ginsenoside Rg1 is the most pharmacological active one. Based on prior experimental results and the understanding of alcoholic hepatitis, the major aim of this study is to investigate whether Rg1 is beneficial in a rodent model mimic alcoholic hepatic injury associated with binge drinking and explore the underlying possible mechanisms. C57BL/6 mice were given oral consumption of 6g/kg alcohol 1h after treated with Rg1 (10, 20 and 40mg/kg) or dexamethasone (1mg/kg) for 9 consecutive days. Biochemical analyses were performed and liver fragments were processed for microscopy, immunohistochemistry and western blot analysis. According to our data, Rg1 treatment significantly reversed the high mortality rate induced by alcohol consumption and also alleviated liver impairment as evidenced by the decrease of serum parameters. Meanwhile, histological and ultrastructural analysis of alcoholic groups showed hepatocellular impairment but restored in Rg1-treated groups. Overproductive inflammatory cytokines were also suppressed by Rg1 in alcohol-intoxicated mouse livers. In addition, changes of GR related NF-κB pathway, including phospho-IκB-α, were also modulated to normal levels. This study demonstrates that Rg1 might promote GR mediating the repression of NF-κB and inhibit the inflammatory reactions in alcoholic hepatitis.